Block copolymer hierarchical structures from the interplay of multiple assembly pathways. Issue 13 (9th March 2020) - Ianiro, Alessandro; Chi, Meng; Hendrix, Marco M. R. M.; Koç, Ali Vala; Eren, E. Deniz; Sztucki, Michael; Petukhov, Andrei V.; de With, Gijsbertus; Esteves, A. Catarina C.; Tuinier, Remco
Abstract : Structurally complex hierarchical block copolymer assemblies can be formed in solution by controlling the interplay of phase separation, crystallization and block segregation with temperature. Abstract : Structurally complex hierarchical block copolymer assemblies can be formed in solution via the interplay of multiple assembly pathways. Crystallizable block copolymers can undergo self-assembly, crystallization or phase separation in solution. By selecting appropriate solvency conditions (solvent and temperature) it is possible to induce an interplay between these processes resulting in a complex association behavior. This leads to the formation of assemblies with up to four levels of hierarchical organization. Furthermore, varying the copolymer composition enables to tune the formation mechanism and the morphology of the aggregates.